2020
DOI: 10.1002/slct.202002399
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Polycaprolactone Scaffolds Using an Ionic Liquid as Alternative Solvent: Morphometric, Mechanical and Biological Properties

Abstract: Ionic liquids (IL) are a greener alternative to aggressive organic solvents used for biopolymers dissolution in the electrospinning process. Nevertheless, the effect of IL on the properties of the electrospun materials is still a gap. In this work, we obtain polycaprolactone (PCL) electrospun mats using two solvents, either trichloromethane (CHCl 3)-a conventional toxic and carcinogenic solvent-or 1-butyl-3-methylimidazolium chloride ([Bmim]Cl), an ionic liquid. The differences between the respective electrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In addition, smooth defect-free nanofibers with a narrow and more uniform diameter distribution are collected using two-component solvent systems. There have already been various solvents used, including benign or green, to prepare the PCL solutions for electrospinning, such as acetone, methanol, formic or acetic acid, or ionic liquids [ 47 , 48 , 49 ]. However, in these solvents it is not possible to achieve the required fiber characteristics (smoothness, small average diameter, uniform); therefore, in the conducted study, the solutions for electrospinning were prepared using a mixture with DCM as a good solvent for PCL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, smooth defect-free nanofibers with a narrow and more uniform diameter distribution are collected using two-component solvent systems. There have already been various solvents used, including benign or green, to prepare the PCL solutions for electrospinning, such as acetone, methanol, formic or acetic acid, or ionic liquids [ 47 , 48 , 49 ]. However, in these solvents it is not possible to achieve the required fiber characteristics (smoothness, small average diameter, uniform); therefore, in the conducted study, the solutions for electrospinning were prepared using a mixture with DCM as a good solvent for PCL.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, [C 2 mim][OAc] is the main ionic liquid utilized as a solvent, followed by 3 that cellulose, silk, and chitin were mostly dissolved in ionic liquids, compared to other natural biodegradable polymers. In addition, synthetic biodegradable polymers, such as PCL and PLA can be dissolved in ionic liquids [4,29]. This proved that the ionic liquids could not only be utilized for dissolving natural polymers but also synthetic polymers.…”
Section: Introductionmentioning
confidence: 97%
“…Figure 1 exhibits the chemical structures of cellulose, cellulose acetate, chitin, and chitosan. Besides this, it can also be seen in Table 1 that synthetic biodegradable polymers, for example, polyhydroxybutyrate (PHB); polycaprolactone (PCL); polylactic acid (PLA); and polyvinyl alcohol (PVA) can be employed for the preparation of electrospun fibers [3,4,29,34]. Moreover, previous studies have shown that natural-synthetic polymer hybrid fibers have also been prepared via the electrospinning method [29,34].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations